2022
DOI: 10.1371/journal.pone.0263920
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening and treatment, HIV infection, and age: Program implementation in seven regions of Namibia

Abstract: The aim of this study was to assess differences in cervical cancer screening and treatment outcomes by HIV status in a routine programmatic setting with a high generalized HIV prevalence. Women living with HIV (WLHIV) are at heightened risk of developing cervical cancer and the World Health Organization recommends all WLHIV who are sexually active be screened, regardless of age. In 2018, Namibia’s Ministry of Health and Social Services introduced a screen-and-treat approach using visual inspection with acetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“… 37 The variability in VIA positivity rates, given its subjective nature, has previously been documented. 38 Our finding that younger women were more likely to be VIA-positive has been demonstrated in a study in Zambia 37 and in a study in Namibia, 36 and is consistent with the epidemiology of HPV being more common in younger women. The association of lower VIA positivity among those on ART was previously demonstrated among WLWHIV in Malawi, 39 and also in a meta-analysis of 31 studies where WLWHIV on ART were less likely to have high-risk HPV or biopsy-confirmed cervical precancer.…”
Section: Discussionsupporting
confidence: 85%
“… 37 The variability in VIA positivity rates, given its subjective nature, has previously been documented. 38 Our finding that younger women were more likely to be VIA-positive has been demonstrated in a study in Zambia 37 and in a study in Namibia, 36 and is consistent with the epidemiology of HPV being more common in younger women. The association of lower VIA positivity among those on ART was previously demonstrated among WLWHIV in Malawi, 39 and also in a meta-analysis of 31 studies where WLWHIV on ART were less likely to have high-risk HPV or biopsy-confirmed cervical precancer.…”
Section: Discussionsupporting
confidence: 85%
“…The peak prevalence of cervical precancerous lesions was observed at 36 -45 years and this is comparable to findings of other studies [18] [19]. A total of 63 (62.4%) clients with cervical precancerous lesions were married, 54 (53.5%) had a parity of ≥3, 47 (46.5%) reported coitarche at less than 18 years, and 78 (77.2%) had a history of multiple sexual The prevalence of suspected cervical cancer in this study was 1.6%, similar to 1.0% in Namibia [18], 0.9% in Malawi [21], and 2.1% in Harare City [23]; however, a lower prevalence of 0.56% was reported among HIV-negative women in rural South Indian women [25]. A bimodal age classification for suspected cancer was noted: 7 (38.9%) for ages 26 -35 years and 36 -45 years; this corresponds to the bimodal age distribution of cervical cancer, with a first peak at age 43 years and a relative rebound at age 61 years, taking into account a 5 -15 year shift from precancerous to full-blown cervical cancer [26].…”
Section: Discussionsupporting
confidence: 82%
“…Multiple sexual partners, age 36 -45 years, and sexually transmitted infections (STIs) were factors found to be associated with precancerous lesions, and these are at par with findings in other studies [18] [19] [21] [22]. After subjecting these factors to multiple logistic regression, STI was found to be a significant predictor of cervical precancerous lesion in this study (OR 1.634, 95% CI: 1.061 -2.518, p-value 0.026).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Perceived benefits of the clinic-based HPV self-sampling were mainly considered to be the visualization of the cervix and free service. An example would be the findings in other studies, where HIV-infected women were motivated to screen for CC at the clinic [9], and all those who were suspected of having the disease completed treatment, compared to the HIV-negative women [28,32]. In Uganda, HIV-infected women are also motivated to be screened at the clinic and by the HW, as this increases the chances for the early diagnosis and treatment of the disease [28].…”
Section: Facilitators Of Hpv-self Sampling Approaches Among Hiv-infec...mentioning
confidence: 99%